Pengaruh Product Development Terhadap Business Growth Kerajinan Batik di Desa Banyubiru Kabupaten Ngawi dengan Peran E-Commerce sebagai Variabel Intervening - Prajogo, Uke (Jurnal Teknologi dan Manajemen Informatika, 2022)
This study aims to determine the effect of product development on the business growth of batik in Banyubiru Village, Ngawi Regency with the role of e-commerce as an intervening variable. The type of research used is explanatory research. The sample in this study was 60 batik craftsmen who were taken by incidental sampling. The research instrument used a questionnaire and observation. The analysis used is multiple regression analysis, where X1 refers to product development variables, Y1 to e-commerce, and Y2 to business growth. Based on the results of the study, it was concluded that product development did not have a positive and significant effect on business growth, and e-commerce did not mediate the effect of product development on business growth.